A metal-porphyrinic framework film as an efficient optical limiting layer in an electro-optical switchable device. Issue 79 (15th September 2021) - Lei, Song; Chang, Li-Mei; Gu, Zhi-Gang; Zhang, Jian
Abstract : Herein we report a 2D surface-coordinated porphyrinic metal–organic framework film (SURMOF) CuTCPP prepared by a layer by layer method as an optical limiting layer in a polymer-dispersed liquid crystal (PDLC) device. Abstract : Herein we report a 2D surface-coordinated porphyrinic metal–organic framework film (SURMOF) CuTCPP prepared by a layer by layer method as an optical limiting layer in a polymer-dispersed liquid crystal (PDLC) device. The results show that the CuTCPP SURMOF/PDLC device has excellent switchable transparency and optical limiting performance, providing a new route to achieve mutilfunctional electro-optical applications.